2009
DOI: 10.1016/j.jfms.2008.12.005
|View full text |Cite
|
Sign up to set email alerts
|

A Nosocomial Outbreak of Feline Calicivirus Associated Virulent Systemic Disease in France

Abstract: This report describes a nosocomial outbreak of feline calicivirus (FCV) associated virulent systemic disease (VSD) in a French veterinary teaching hospital in 2005. The outbreak started in March and resolved within 1 month. Signs, clinical course, clinicopathological findings and lesions were typical of FCV-induced VSD. FCV infection was confirmed by quantitative reverse transcriptase-polymerase chain reaction (RT-PCR). Among the eight infected cats, two had to be euthanased, three died, and three recovered af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1
15

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 30 publications
4
49
1
15
Order By: Relevance
“…Feline calicivirus causes URTD and oral mucosal ulceration, and can cause ocular surface disease, primarily conjunctivitis. In some outbreaks of virulent systemic FCV, large percentages of cats have died (Hurley et al, 2004;Coyne et al, 2006;Reynolds et al, 2009) Feline calicivirus has been cited as causing only mild conjunctivitis (Ramsey, 2000). However, a recent study of 99 cats with URTD, as well as ocular surface disease, found that ocular samples analyzed using PCR were positive for FCV alone in 11 (11.1%) cats; in 19 (19.2%) cats, FCV was present with other infectious agents, including FHV-1 (Gerriets et al, 2012).…”
Section: Clinical Signsmentioning
confidence: 99%
“…Feline calicivirus causes URTD and oral mucosal ulceration, and can cause ocular surface disease, primarily conjunctivitis. In some outbreaks of virulent systemic FCV, large percentages of cats have died (Hurley et al, 2004;Coyne et al, 2006;Reynolds et al, 2009) Feline calicivirus has been cited as causing only mild conjunctivitis (Ramsey, 2000). However, a recent study of 99 cats with URTD, as well as ocular surface disease, found that ocular samples analyzed using PCR were positive for FCV alone in 11 (11.1%) cats; in 19 (19.2%) cats, FCV was present with other infectious agents, including FHV-1 (Gerriets et al, 2012).…”
Section: Clinical Signsmentioning
confidence: 99%
“…Infection is generally associated with relatively mild oral and respiratory tract disease. However, the virus's genetic plasticity has led to the repeated emergence of variants (or pathotypes), some of which can be lethal (8,18,25,33,42,43). In addition to its significance for feline health, FCV is frequently used as a model for human norovirus, an important cause of vomiting and diarrhea in people (36).…”
mentioning
confidence: 99%
“…239 In most cases, this dissemination does not manifest clinically. 132, 223,247,260 This syndrome involves widespread vasculitis and multiorgan failure and has occurred in vaccinated animals. Lameness associated with acute synovitis may occur, and although the precise mechanism of disease remains unclear, viral antigen associated with joint macrophages has been identified.…”
Section: Feline Calicivirusmentioning
confidence: 99%